2019
DOI: 10.1103/physreve.100.032704
|View full text |Cite
|
Sign up to set email alerts
|

Orientational ordering and layering of hard plates in narrow slitlike pores

Abstract: We examine the ordering behavior of hard plate-like particle in a very narrow slit-like pore using the Parsons-Lee density functional theory and the restricted orientation approximation.We observe that the plates are orientationally ordered and align perpendicularly (face-on) to the walls at low densities, a first order layering transition occurs between uniaxial nematic structures having n and n+1 layers at intermediate densities and even a phase transition between a monolayer with parallel (edge-on) orientat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 76 publications
1
5
0
Order By: Relevance
“…Here L is the length of the particle, and D is its short side. Despite some sharp differences, some similar results have also been achieved for hard plate-like particles [31,[44][45][46][47].…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Here L is the length of the particle, and D is its short side. Despite some sharp differences, some similar results have also been achieved for hard plate-like particles [31,[44][45][46][47].…”
Section: Introductionsupporting
confidence: 68%
“…The nematic planar phase confined between two walls could be uniaxial (U) or biaxial (B). The U-B transition induced by a substrate(s) has been predicted to be second order for confined hard rod-like [27][28][29][30] and plate-like [31] particles. The biaxial nematic phases have been studied widely experimentally [32][33][34] and theoretically [35][36][37] due to their fast response time to the applied electric field, which is an essential factor in display technologies [38].…”
Section: Introductionmentioning
confidence: 99%
“…The properties of fluids are modified by physical confinement. Confinement changes, for example, the structure and phase behaviour, [1][2][3][4][5][6][7][8][9][10][11][12] dynamics and viscoelasticity, [12][13][14][15][16] and glass transition. [17][18][19][20][21][22][23][24] It affects atomic, molecular, as well as colloidal fluids.…”
Section: Introductionmentioning
confidence: 99%
“…By applying Onsager second-order virial theory, Velasco and co-workers studied the effect of constraining perfectly aligned hard boardlike particles (HBPs) within two parallel planar hard walls and observed suppression of the nematic-to-smectic transition, usually observed in the bulk, and the occurrence of biaxial phases 43 . A similar study was performed by Mizani et al, who applied Parsons-Lee density functional theory within the restricted-orientation Zwanzig model to study the orientational ordering and layering of HBPs in slit pores 8 . These authors observed that the hard wall-particle interaction promotes the occurrence of uniaxial nematic order with strong adsorption at the walls.…”
Section: Introductionmentioning
confidence: 87%
“…In case of nanopore-confined colloids, these deviations are especially significant when the size of the suspended particles or macromolecules is comparable to the size of the hosting nanopore. Experimental [1][2][3][4][5] , theoretical [6][7][8][9][10][11] and simulation [12][13][14][15][16][17][18][19][20][21] studies on confined colloidal suspensions have shown the existence of a rich realm of nanostructures that are not observed in the bulk. Additionally, depending on the adhesive interactions established between the fluid and the pore walls and their relevance with respect to the cohesive interactions between fluid particles, several new phenomena, such as wetting, capillary condensation and evaporation, layering, anchoring, are detected [22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%